Anmeldelse af Joachim Böger, Helmut Diekmann, Harmut Lenk & Caren Schröder: Suomi-saksa opiskelusanakirja ('Finsk-tysk studieordbok') - Fuchs, Bertold (LexicoNordica, 2000)
Anmeldt værk: Joachim Böger, Helmut Diekmann, Harmut Lenk & Caren Schröder: Suomi-saksa opiskelusanakirja ('Finsk-tysk studieordbok'). Helsinki/ Porvoo/Juva: WSOY 1999.